Share price behavior of Nepalese insurance companies - Khadka, Ajaya Kumar; Khadka, Srijana (NCC Journal, 2021)
This research explores the influencing factors of market share price behavior in the Nepalese insurance business. The study focuses on four insurance firms and utilizes a purposive sample approach, yielding a dataset of 40 observations. The research investigates the correlations between significant factors such as dividend payout ratio (DPR), Earnings per share (EPS), price–earnings ratio (PER), dividend per share (DPS), and market price per share (MPS). The data show strong relationships between these characteristics and the MPS. The DPR and MPS have a negative connection, indicating that increased dividend distributions may lead to lower market prices. Positive correlations, on the other hand, are discovered among EPS, PER, DPR, and MPS, indicating that investors appreciate firms with greater profitability, growth prospects, and dividend payments. The research adds to the knowledge of share price behavior in Nepalese insurance firms. However, it is crucial to note that the findings are based on small sample size and may not apply to other sectors or countries. To fully understand the factors determining market pricing, future research should investigate increasing the sample size and including longitudinal approaches. These results have practical ramifications for investors, insurers, and politicians. Understanding share price behavior allows stakeholders to make educated choices about investment strategies, financial performance assessment, and policy creation to improve economic performance and shareholder value in Nepal's insurance business.